Telomerase inhibition in malignant gliomas: a systematic review. (15th March 2023) - D'Alessandris, Quintino Giorgio; Battistelli, Marco; Pennisi, Giovanni; Offi, Martina; Martini, Maurizio; Cenci, Tonia; Falchetti, Maria Laura; Lauretti, Liverana; Olivi, Alessandro; Pallini, Roberto; Montano, Nicola
Abstract: Glioblastoma (GBM) is the most frequent adult malignant brain tumour and despite different therapeutic efforts, the median overall survival still ranges from 14 to 18 months. Thus, new therapeutic strategies are urgently needed. However, the identification of cancer-specific targets is particularly challenging in GBM, due to the high heterogeneity of this tumour in terms of histopathological, molecular, genetic and epigenetic features. Telomerase reactivation is a hallmark of malignant glioma. An activating mutation of the hTERT gene, encoding for the active subunit of telomerase, is one of the molecular criteria to establish a diagnosis of GBM, IDH-wildtype, in the 2021 WHO classification of central nervous system tumours. Telomerase inhibition therefore represents, at least theoretically, a promising strategy for GBM therapy: pharmacological compounds, as well as direct gene expression modulation therapies, have been successfully employed in in vitro and in vivo settings. Unfortunately, the clinical applications of telomerase inhibition in GBM are currently scarce. The aim of the present systematic review is to provide an up-to-date report on the studies investigating telomerase inhibition as a therapeutic strategy for malignant glioma in order to foster the future translational and clinical research on this topic.